Convict Depot Carrera Isle. Trinidad - (:unkn) unknown (Muir Marshall and Co.,[Trinidad and Tobago], 2011)
The postcard shows Carrera Island, referred to as Convict Depot because during the 1800s prisoners were carried to the island to quarry limestone for road building. In 1877, a prison was constructed, today the island remains a prison island. This postcard is addressed to Alfred C. Place, Esq. and affixed are two half penny postage stamp. This card is post marked 1907.
Colour: Coloured; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; 1907; Correctional institutions--Trinidad and Tobago; Prisons--Trinidad and Tobago; Islands--Trinidad and Tobago; Carrera Island